AN ANALYSIS OF TOXIC RELATIONSHIP REPRESENTATION IN IT ENDS WITH US NOVEL BY COLLEEN HOOVER - Ayu; Ramasari, Maria; Hamdan (LP3MKIL, 2023)
This study was about an analysis of toxic relationship representation between the main characters in It Ends with Us novel by Colleen Hoover. This study would answer the question “What kind of toxic relationship form experienced by the main character in It Ends with Us novel by Colleen Hoover. By answering the question the writer would know what kind of toxic relationship was found in the novel. The writer used descriptive qualitative research. The object of the study was a novel entitled It Ends with Us by Colleen Hoover. The instrument of this study was the writer herself as the human instrument key. In collecting the data, the writer read the novel highlighted and underlined those sentences and quotations from the novel and the last rewrote them in another book. In analyzing the data, the writer identified the data, categorized and classified all data in the novel, reduced the data, and described and interpreted the data. There is a point explained in the novel. The writer found about Toxic Relationship in the novel and it is divided into seven parts. Deprecator Belittler, the Bad Temper Toxic Partner, the Guilt Inducer, the Overreacted, the Dependent Partner, the Independent Toxic Controller and the Possessive Toxic Controller.